Interplay between RNA viruses and cGAS/STING axis in innate immunity - Amurri, Lucia; Horvat, Branka; Iampietro, Mathieu (Frontiers in Cellular and Infection Microbiology, 2023)
While the function of cGAS/STING signalling axis in the innate immune response to DNA viruses is well deciphered, increasing evidence demonstrates its significant contribution in the control of RNA virus infections. After the first evidence of cGAS/STING antagonism by flaviviruses, STING activation has been detected following infection by various enveloped RNA viruses. It has been discovered that numerous viral families have implemented advanced strategies to antagonize STING pathway through their evolutionary path. This review summarizes the characterized cGAS/STING escape strategies to date, together with the proposed mechanisms of STING signalling activation perpetrated by RNA viruses and discusses possible therapeutic approaches. Further studies regarding the interaction between RNA viruses and cGAS/STING-mediated immunity could lead to major discoveries important for the understanding of immunopathogenesis and for the treatment of RNA viral infections.